Analysis of the Performance of an Air-Powered Energy-Harvesting Pavement. Issue 1 (January 2015) - Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro
Current energy-harvesting pavements do not have the features needed for large-scale applications. For example, the use of water as an operating fluid may create problems with the pavement structure if leakage occurs. Moreover, the design of such systems is not trivial, as the systems need auxiliary machinery to work (e.g., pumps or additional heaters to control the temperature of the working fluid). These problems can be solved if air is used as the operating fluid. This paper presents the prototype of an energy-harvesting pavement that uses air as the operating fluid and has been built, tested, and analyzed. The prototype consists of a set of pipes buried in an aggregate layer that is covered by a layer of a dense asphalt mixture. The pipes are connected to an updraft chimney. The pavement surface is irradiated with infrared light; thus, heat travels through the layers until it reaches the air in the pipes. Through natural convection, air flows through the chimney. The prototype provides satisfactory thermal properties that show a noticeable withdrawal of energy. The performance of the prototype is heavily influenced by the height of the chimney. Moreover, an air mass flow ranging from 0 (obstructed pipes) to 0.5 m/s (chimney 1 m high) is measured. Analysis of the results shows that the prototype proved useful in reducing the urban heat island effect by lowering the pavement surface temperature by more than 6°C.